KELELAHAN DAN TEGANGAN YANG DIIZINKAN PADA SAMBUNGAN LAS - Rifan, Kemas (Mesin, 2017)
Welded joints loaded cyclically are prone to fatigue because they provide srress concentrations due to geometry changes, weld proï¬le shapes and microscopic defects in the welds". Allowable stresses for welded joints under cycliuzlly loading must be based on empirical values.